Characterization of Chemical and Physical Properties of Hydroxypropylated and Cross-linked Arrowroot (Marantha arundinacea) Starch - Rijanti Rahaju Maulani; Dedi Fardiaz; Feri Kusnandar; Titi Candra Sunarti (Institute for Research and Community Services, Institut Teknologi Bandung, 2013)
The modern food industry and a variety of food products require tolerant starch as raw material for processing in a broad range of techniques, from preparation to storage and distribution. Dual modification of arrowroot starch using hydroxypropylation and cross-linking was carried out to overcome the lack of native arrowroot starch in food processing application. The modifications applied were: combined propylene oxide (8%, 10%, and 12%); sodium tri meta phosphate/STMP (1%, 2%, and 3%); and sodium tri poly phosphate/STPP (4%, 5%, and 6%). These modifications significantly affected the composition of the amylose and amylopectin and the amount of phosphorus in the granules. Higher amounts of phosphate salt gave a higher phosphorus content, which increased the degree of substitution (DS) and the degree of cross-link. Arrowroot starch that was modified using a concentration of 8-10% propylene oxide and 1-2% STMP : 3-5% STPP produced a starch with < 0.4% phosphorus content. A higher concentration of propylene oxide provided a higher degree of hydroxypropyl. The changed physical properties of the modified granular arrowroot starch were examined through SEM testing, and its changed crystalline patterns through X-ray diffraction measurements. Especially, provision of a high concentration of propylene oxide (12%) combined with 3% STMP : 6% STPP affected the granular morphology and the crystallinity.